Inhibition of TMEM16A by Natural Product Silibinin: Potential Lead Compounds for Treatment of Lung Adenocarcinoma - Guo, Shuai; Bai, Xue; Liu, Yufei; Shi, Sai; Wang, Xuzhao; Zhan, Yong; Kang, Xianjiang; Chen, Yafei; An, Hailong (Frontiers in Pharmacology, 2021)
Background: Effective anticancer therapy can be achieved by identifying novel tumor-specific drug targets and screening of new drugs. In recently, TMEM16A has been identified overexpressed in lung adenocarcinoma, and inhibitors of TMEM16A showed obvious antitumor efficacy. Methods: YFP fluorescence quenching and whole cell patch clamp experiments were used to explore the inhibitory effect of silibinin on TMEM16A. Molecular docking and site-directed mutagenesis were performed to confirm the binding sites of silibinin and TMEM16A. MTT assay, wound healing assay and Annexin-V assay were used to detect the effect of silibinin on cancer cell proliferation, migration and apoptosis. shRNA was transfected into LA795 cells to knock down the expression of endogenous TMEM16A. Tumor xenograft mice combined with western blot experiments reveal the inhibitory effect and mechanism of silibinin in vivo. Results: Silibinin concentration-dependently inhibited the whole-cell current of TMEM16A with an IC50 of 30.90±2.10 μM. The putative binding sites of silibinin in TMEM16A were K384, R515 and R535. The proliferation and migration of LA795 cells were down-regulated by silibinin, and the inhibition effect can be abolished by knockdown of the endogenous TMEM16A. Further, silibinin was injected to tumor xenograft mice which exhibited significant antitumor activity without weight loss. Finally, western blotting results showed the mechanism of silibinin inhibiting lung adenocarcinoma was through apoptosis and down-regulation of cyclin D1. Conclusion: Silibinin is a novel TMEM16A inhibitor, and it can be used as a lead compound for the development of lung adenocarcinoma therapy drugs.